2021
DOI: 10.51836/jedma.v1i2.155
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Brain Based Learning Terhadap Hasil Belajar Siswa

Abstract: Untuk melihat peningkatan siswa dalam proses pembelajaran, salah satunya adalah  nilai hasil belajar. Supaya membuat siswa berperan aktif dalam proses pembelajaran materi segi empat bangun trapesium di kelas, maka dapat menerapkan model Brain Based Learning dimana siswa diminta aktif untuk menggali pengetahuan agar dapat meningkatkan hasil belajar. Penelitian ini bertujuan untuk mengetahui adanya pengaruh model Brain Based Learning terhadap hasil belajar siswa pada materi segi empat. Penelitian ini adalah eksp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
1
0
4
Order By: Relevance
“…From this research it was obtained regarding Flipped Classroom learning devices on the material of harmonic vibration and impulse and momentum, it can be concluded that the resulting learning devices are stated to be valid, practical, interesting, easy and useful to apply in learning physics in high school, but have a low level of effectiveness in improve student learning outcomes. Supported by other study that conducted a study on learning using the flipped classroom model (Syarifudin et al, 2021). From this study, the research results showed that the learning process was in the very good category, the learning outcomes of students were in the sufficient category.…”
Section: Discussionsupporting
confidence: 55%
“…From this research it was obtained regarding Flipped Classroom learning devices on the material of harmonic vibration and impulse and momentum, it can be concluded that the resulting learning devices are stated to be valid, practical, interesting, easy and useful to apply in learning physics in high school, but have a low level of effectiveness in improve student learning outcomes. Supported by other study that conducted a study on learning using the flipped classroom model (Syarifudin et al, 2021). From this study, the research results showed that the learning process was in the very good category, the learning outcomes of students were in the sufficient category.…”
Section: Discussionsupporting
confidence: 55%
“…Salah satu sifat peserta didik pada jenjang MI/SD adalah rasa ingin tahu yang tinggi. Jika peserta didik menghadapi masalah, mereka akan tertarik untuk menyelesaikannya (Syarifudin et al, 2021).…”
Section: C) Implementasi Model Problem Based Learning Pada Muatan Bah...unclassified
“…Berdasarkan hasil penelitian yang telah dijabarkan sebelumnya menunjukkan bahwa hipotesis pertama yaitu pengaruh model Problem Based Learning (PBL) terhadap hasil belajar matematika bilangan bulat peserta didik kelas VI di SD Negeri Desa Dodap diperoleh Ha diterima dan H0 ditolak. Hal ini sejalan dengan penelitian sebelumnya (Syarifudin et al, 2021) yang mengungkapkan bahwa model pembelajaran Problem Based Learning (PBL) dapat meningkatkan hasil belajar mulai dari 5% sampai pada 95%. PBL dapat berjalan dengan baik ketika guru melibatkan peserta didik dengan stimulus yang tepat (Asrifah et al, 2020) (Paradina et al, 2019).…”
Section: Pembahasanunclassified